Effect of Nutrient Management on the Growth and Yield of Cabbage (Brassica oleracea var. capitata L.) in Calcareous Soils of Bangladesh - Naher, M N A; Alam, M N; Jahan, N (The Agriculturists, 2015)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> An investigation was carried out in the calcareous soil of Chapai Nawabganj belonging to the High Ganges River Floodplain during November 2008 to March 2009 to examine the effect of different macro and micronutrients (N, P, K, S, Zn, B and Mo at 150, 50, 100, 20, 3, 3 and 1 kg/ha, respectively) on the growth and yield of cabbage. Application of different nutrients exhibited significant influence on the growth and yield of cabbage. The highest plant spread (70.76 cm), height (37.89 cm), leaf length (37.83 cm), leaf breadth (27.13 cm), head thickness (12.85 cm), head diameter (23.02 cm), marketable head yield (76.53 t/ha) which is 191% increase over control), early head formation and maturity were recorded from the plot receiving N, P, K and B at the rate of 150, 50, 100 and 3 kg/ha, respectively. The treatment N, P, K and S showed the highest weight of loose leaves (640 g/plant) and decreased the weight of folded leaves or head weight, whereas, the treatment N, P, K and B increased the folded leaves or maximum head weight (1894.18 g/plant). The Agriculturists 2014; 12(2) 24-33 <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->